Teaching science process skill using guided inquiry model with starter experiment approach: an experimental study - Ika Wardani; D. Djukri (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Numerous challenges occur in education field require effective solutions to encounter. The aim of this research was to investigate the effectiveness of guided inquiry model with starter experiment approach in teaching science process skill. This quasi-experimental research employed non-equivalent control group design. A total of 64 students of X MIPA1 and X MIPA5 was selected as the sample. In selecting the sample, the researchers applied cluster random sampling while the data was collected by using test. The data was analyzed using ANCOVA after underwent prerequisite normality and homogeneity tests (α = 0.05). The results showed that the mean of posttest was 79.33%. The improvement of science process skill was 44.88%, compared to the pretest results. The results of ANCOVA revealed that the significance value was of 0.025. This means that the guided inquiry model with starter experiment approach in teaching science process skill of the students is effective.